Proses Penanganan Clearance Out Kapal Ternak Berbendera Asing Dengan Inaportnet Oleh Pt. Pelayaran Semesta Sejahtera Lestari Belawan - Riski Ronaldo Saragih; Syarifur Ridho; Yuris Danilwan; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Pelayaran Semesta Sejahtera Lestari Belawan is a company that operates as a shipping agency (ship agency) which provides domestic and international services. The process of handling ship departure (clearance out) at PT. The Semesta Sejahtera Lestari Belawan voyage starts when the ship has finished carrying out activities at the port, the agent makes another request for ship departure or Clearance Out. The Clearance Out process is a maximum of six hours before the ship leaves, the agent submits a ship out service in the Inaportnet system. To issue an SPB (Sailing Approval Letter), the agent must complete all documents and costs which are the agent's responsibility. For the issuance of an SPK (Work Order), guide the ship out no later than one hour after the SPB (Sailing Approval Letter) is issued. After processing the SPB (Sailing Approval Letter) is complete, the agent will take the ship documents and SIB (Sailing Permit) at KSOP. PT Pelayaran Semesta Sejahtera Lestari is a company that operates in the service and agency services sector, in other words a representative of the general agent/principle to take care of ship documents and take care of all ship needs that are needed when the ship is at the port. To obtain data, the author used field research and library research methods.